Green Fibers-Reinforced Cement Mortar with the Inclusion of Nano-CaCO3 and Metakaolin - HAMAD, Ali Jihad; SLDOZIAN, Rami Joseph; KADHIM, Ruqaya F. (Engineering Transactions, 2024)
Over the previous few decades, there has been a noticeable increase in interest in the use of vegetable fibers and supplemental cementitious elements in mortar and concrete. The date palm frond was utilized in this study to create date palm fibers (DPF), which were then added to the cement mortar at percentages of 1%, 2%, 3%, 4%, and 5% by cement weight. There were two types of DPFs used: one type was untreated, and the other had a mechanical treatment that created holes before applying a layer of polychloroprene (neoprene) on the surface. Metakaolin (MK) and nano calcium carbonate (nano-CaCO3) were added to the cement mortar by the weight of cement. MK was replaced by 10% of the weight of cement. Besides, the nano-CaCO3 was replaced by 1%, 2%, 3%, and 4% of the weight of cement. Mechanical tests for flowability, compressive strength, and flexural strength were conducted. In addition, one MCDM methodology called VIKOR is utilized to choose the best combination out of several combinations and criteria. The results indicate that a higher DPF concentration enhances both compressive and flexural strength. The mixtures with the DPF coating and mechanical treatment give the strongest and most significant results. In addition, the flowability of cement mortar decreases when the DPF concentration increases. In addition to the high content of nano-CaCO3 in cement mortar, given the grater reading of strength, the presence of nano-CaCO3 in cement mortar reduces the disparity in result values that have a higher DPF content. The mixtures containing 4% and 5% DPF and 3% and 4% nano-CaCO3 are the optimal ones, according to the VIKOR technique.